2021
DOI: 10.3390/antiox10081181
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidative, Oxidoreductive and Detoxification Enzymes during Development of Aphids and Temperature Increase

Abstract: Temperature, being the main factor that has an influence on insects, causes changes in their development, reproduction, winter survival, life cycles, migration timing, and population dynamics. The effects of stress caused by a temperature increase on insects may depend on many factors, such as the frequency, amplitude, duration of the stress, sex, or the developmental stage of the insect. The aim of the study was to determine the differences in the enzymatic activity of nymphs and adult aphids Aphis pomi, Macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
(69 reference statements)
0
12
0
1
Order By: Relevance
“…Our research indicates that this method could be used to discriminate against aphid species, but more research is needed. Many studies show that the chemical composition of the insect’s body changes during its life cycle, depending on gender, and adapts to unfavorable environmental conditions, e.g., the season [ 32 , 39 , 40 ]. Therefore, as in the case of plant material, it is important to properly collect and prepare samples for FTIR analysis, taking into account all these factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research indicates that this method could be used to discriminate against aphid species, but more research is needed. Many studies show that the chemical composition of the insect’s body changes during its life cycle, depending on gender, and adapts to unfavorable environmental conditions, e.g., the season [ 32 , 39 , 40 ]. Therefore, as in the case of plant material, it is important to properly collect and prepare samples for FTIR analysis, taking into account all these factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant defense system of aphids is also influenced by temperature. Durak et al [ 74 ] and Dampc et al [ 75 ] showed that an increase in temperature caused alterations in SOD and CAT activity, which were highest at 28 °C, in Aphis pomi (De Geer), Macrosiphum rosae (L.) and Cinara cupressi (Buckton). Khursid et al [ 69 ] stated that SOD and CAT activity in M. persicae adults increased under short-term heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Pada nimfa dicirikan oleh peningkatan enzim antioksidan (superokside dismutase dan katalase) sedangkan pada imago, terjadi peningkatan enzim detoksifikasi (βglucosidase & glutathiones-transferase) dan oksidoreduktif (polifenol oxidase & peroxidase). Peningkatan enzim tersebut akan mengurangi umur panjang serangga (Durak et al, 2021) Trogoderma granarium,[36][37][38][39][40][41][42][43][44][45][46][47] keduanya memiliki perkembangan yang berbeda nyata pada kandungan nutrisi yang berbeda (Cox & Collins, 2001)…”
Section: Analisis Kekerasan Singkong Keringunclassified